Regulation of PPARγ Coactivator-1α Function and Expression in Muscle: Effect of Exercise - Giulia Uguccioni; Donna D'souza; David A. Hood (PPAR Research)
PPARγ coactivator-1α (PGC-1α) is considered to be a major regulator of mitochondrial biogenesis. Though first discovered in brown adipose tissue, this coactivator has emerged as a coordinator of mitochondrial biogenesis in skeletal muscle via enhanced transcription of many nuclear genes encoding mitochondrial proteins. Stimuli such as exercise provoke the activation of signalling cascades that lead to the induction of PGC-1α. Posttranslational modifications also regulate the function of PGC-1α, with a multitude of upstream molecules targeting the protein to modify its activity and/or expression. Previous research has established a positive correlation between resistance to fatigue and skeletal muscle mitochondrial content. Recently, studies have begun to elucidate the specific role of PGC-1α in exercise-related skeletal muscle adaptations, with several studies identifying it as a dominant regulator of organelle synthesis. This paper will highlight the function, regulation, and expression of PGC-1α, as well as the role of the coactivator during exercise adaptations.